2015
DOI: 10.2147/ijn.s78995
|View full text |Cite
|
Sign up to set email alerts
|

Targeted tumor imaging of anti-CD20-polymeric nanoparticles developed for the diagnosis of B-cell malignancies

Abstract: The expectations of nanoparticle (NP)-based targeted drug delivery systems in cancer, when compared with convectional therapeutic methods, are greater efficacy and reduced drug side effects due to specific cellular-level interactions. However, there are conficting literature reports on enhanced tumor accumulation of targeted NPs, which is essential for translating their applications as improved drug-delivery systems and contrast agents in cancer imaging. In this study, we characterized biodegradable NPs conjug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The renal localization of Ergidina cannot be attributed to the clearance of the molecule, because its molecular weight of approximately 120 kDa is well above the size limit of the molecules filtering through the glomeruli under physiologic conditions. The weak fluorescent signal observed in the bladder is due to small amount of free fluorescent dye excreted in the urine (20, 27). A plausible explanation for the preferential homing of the neutralizing anti-C5 antibody to the kidney is that the recombinant molecule interacts with integrins expressing RGD-binding sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The renal localization of Ergidina cannot be attributed to the clearance of the molecule, because its molecular weight of approximately 120 kDa is well above the size limit of the molecules filtering through the glomeruli under physiologic conditions. The weak fluorescent signal observed in the bladder is due to small amount of free fluorescent dye excreted in the urine (20, 27). A plausible explanation for the preferential homing of the neutralizing anti-C5 antibody to the kidney is that the recombinant molecule interacts with integrins expressing RGD-binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…A small-animal time-domain Optix MX preclinical NIR-imager (Advanced Research Technologies) equipped with a pulsed laser diode and a time-correlated single photon counting detector was used in this study for the in vivo and ex vivo evaluation of labeled Ergidina distribution, as previously detailed (20). …”
Section: Methodsmentioning
confidence: 99%
“…ese kinds of antibodies are made of two different monomers, which, due to a knob into hole mechanism, are able to self-assemble in a scFv-Fc antibody [119]. According to this strategy, a bispecific antibody can be generated, one arm of the molecule with an antigen tissue specificity and the other one able to block an inflammatory cytokine [3] or a protein of the complement system [120].…”
Section: Recombinant Antibodies Andmentioning
confidence: 99%
“…is process can affect the efficacy of NPs to effectively reach their target and exert a therapeutic effect [1], as well as potentially increase the risk of unwanted liver toxicity [2]. Biodistribution studies have demonstrated that the clearance action exerted by the liver is confirmed for the majority of NP designs: polymeric NPs [3][4][5], micelles [6,7], quantum dots [8], gold NPs [9], and carbon nanotubes [10]. In this context, injected nanomaterials usually accumulate in the liver and in an amount that depends on their physiochemical properties, such as size, shape, and surface functionalization, although relatively little is understood about dynamics of NP transport at the intraorgan level [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Capolla and colleagues also used an anti-CD20 antibody functionalized into polymeric-fluorophore Cy5.5-labeled NPs for in vivo imaging directed at the diagnosis of B-cell malignancies. These NPs might also be used as a personalized treatment strategy by loading with drugs, becoming an attractive theranostics platform (Table 1 ) (Capolla et al, 2015 ). Besides CD20 antigens, CD45 and CD19 are the two most common surface proteins expressed by B-cells and used in diagnostic immunophenotyping.…”
Section: Nps Applications In Liquid Tumorsmentioning
confidence: 99%